Seismic Characterisation of Gas-rich Near Surface Sediments in the Arkona Basin, Baltic Sea - Mathys, M.; Thießen, O.; Theilen, F.; Schmidt, M. (Marine geophysical researches, 2005)
Gas in sediments has become an important subject of research for various reasons. It affects large areas of the sea floor where it is mainly produced. Gas and gas migration have a strong impact on the environmental situation as well as on sea floor stability. Furthermore, large research programs on gas hydrates have been initiated during the last 10 years in order to investigate their potential for future energy production and their climatic impact. These activities require the improvement of geophysical methods for reservoir investigations especially with respect to their physical properties and internal structures. Basic relationships between the physical properties and seismic parameters can be investigated in shallow marine areas as they are more easily accessible than hydrocarbon reservoirs. High-resolution seismic profiles from the Arkona Basin (SW Baltic Sea) show distinct 'acoustic turbidity' zones which indicate the presence of free gas in the near surface sediments. Total gas concentrations were determined from cores taken in the study area with mean concentrations of 46.5 ml/l wet sediment in non-acoustic turbidity zones and up to 106.1 ml/l in the basin centre with acoustic turbidity. The expression of gas bubbles on reflection seismic profiles has been investigated in two distinct frequency ranges using a boomer (600-2600 Hz) and an echosounder (38 kHz). A comparison of data from both seismic sources showed strong differences in displaying reflectors. Different compressional wave velocities were observed in acoustic turbidity zones between boomer and echosounder profiles. Furthermore, acoustic turbidity zones were differently characterised with respect to scattering and attenuation of seismic waves. This leads to the conclusion that seismic parameters become strongly frequency dependent due to the dynamic properties of gas bubbles.[PUBLICATION ABSTRACT]